1981
DOI: 10.3109/00365598109179616
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized Renal Cell Carcinoma

Abstract: In an autopsy series comprising 235 clinically unrecognized renal cell carcinoma metastatic spread was revealed in 24%. The number of metastasizing tumours increased significantly with the size of the primary tumour. Local aggressiveness of the primary tumour was more common for large tumours but was much more closely correlated to metastatic spread than to size. Tumours ingrowth in the renal vein was significantly commoner in metastasizing tumours as compared to non-metastasizing tumours. The study confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…In the Hradec Králové area, the incidence was largely constant (1.55%). In the study performed by Hellsten et al [10, 11] in Malmö, 350 RCCs were found among 16,294 autopsies (2.15%) from 1958 to 1969. In 115 cases (32.9%) the RCCs were clinically recognized and 235 (67.1%) were clinically unrecognized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Hradec Králové area, the incidence was largely constant (1.55%). In the study performed by Hellsten et al [10, 11] in Malmö, 350 RCCs were found among 16,294 autopsies (2.15%) from 1958 to 1969. In 115 cases (32.9%) the RCCs were clinically recognized and 235 (67.1%) were clinically unrecognized.…”
Section: Discussionmentioning
confidence: 99%
“…It is uncertain up to now, whether this increase of incidence is reality or not. In a series of 16,294 autopsies in Malmö, 350 RCCs were detected by Hellsten et al [10, 11, 12] during the years 1958–1969. Of these tumors, 235 (67.14%) were clinically unrecognized.…”
Section: Introductionmentioning
confidence: 99%
“…Hölzel u. Altwein beschrieben für Deutschland eine Zunahme der Nierenzellkarzinom-Inzidenz in den letzten Jahren um 15 bis 20 % [10] [8,9]. Somit muû von einer hohen Rate sogenannter inzidenteller Nierenkarzinome ausgegangen werden.…”
Section: Nierenzellkarzinom · Inzidenz · Ultraschallunclassified
“…The annual rate of the incidentally found carcinomas has increased up to 70% [10]. However, in a series of 16,294 autopsies in Malmö out of 350 RCCs (67.14%) revealed by Hellsten et al [12][13][14] during the years of 1958-1969 235 RCC were clinically unrecognized. Among the 235 clinically unrecognized tumors 56 cases (24%) with metastatic spread were revealed.…”
Section: Introductionmentioning
confidence: 99%